Elevation-induced changes in soil sulfur availability in tea plantations - Hong Wang; Chen Qian; Hiba Shaghaleh; Jianfei Wang; Xiaoliang Li; Sumei Duan; Cece Qiao; Yousef Alhaj Hamoud (Frontiers in Plant Science)
Chinese tea plantations, as the world’s leading tea producers, face escalating challenges such as soil acidification and nutrient management. Investigating soil nutrient variations along elevation gradients is crucial. Despite extensive research on macronutrients like carbon, nitrogen, and phosphorus, the role of available sulfur (AS), tightly interlinked with other nutrients, remains underexplored. This study focuses on available S dynamics in Huoshan County, Anhui Province, utilizing soil and litter samples collected from tea plantations at diverse elevations. The results revealed non-linear variations of soil AS with altitude and principal component (PC1) of other soil properties, significantly influencing tea plantation segregation by elevation. Available S exhibited heightened sensitivity to elevation changes compared to other nutrients, underscoring its pivotal role in tea plantation management and soil nutrient cycling. Furthermore, tea plantation dimensions notably decreased with increasing altitude. These findings emphasize the importance of available S in tea garden nutrient management and suggest its crucial consideration in future research and management endeavors. The non-linear correlation between available S and PC1 highlights the responsiveness of available S to elevation variations, emphasizing its significance in tea plantation soil dynamics. This study offers valuable insights into optimizing nutrient management strategies in tea plantations amidst elevation gradients.